2013
DOI: 10.1371/journal.pone.0062347
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of the Tumor-Sensitive Calmodulin-Like Protein CALML3 in Normal Human Skin and Hyperproliferative Skin Disorders

Abstract: Background and ObjectiveCalmodulin-like protein CALML3 is an epithelial-specific protein regulated during keratinocyte differentiation in vitro. CALML3 expression is downregulated in breast cancers and transformed cell lines making it an attractive marker for tumor formation. The objective of this study was to survey CALML3 localization in normal epidermis and in hyperproliferative skin diseases including actinic keratosis, squamous and basal cell carcinoma as well as verruca and psoriasis and to compare CALML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Twenty‐nine studies provided molecular/genetic/immunological evidence relevant to inform a field definition in AK (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐nine studies provided molecular/genetic/immunological evidence relevant to inform a field definition in AK (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…CALML3, an epithelial-specific calcium-sensing protein, has also been identified as being an up-regulated and promoter-hypomethylated gene. CALML3, which is expressed at high levels in normal epithelium, has also been shown to be down-regulated during malignant transformation, and it thus assumed to be a biomarker of terminally differentiated epithelium (38,39). It has been shown that specific DNA hypomethylation at gene promoter regions plays a crucial role in tumorigenesis through the up-regulation of oncogenes, such as Rras in gastric cancer and cyclin D2 in pancreatic cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…PRRX1 (31, 32), RAB38 (33), FAP (34, 35), GCNT2 (36), and ASB4 (37) have been associated with tumor progression. By contrast, CALML3 has been documented as a marker in well-differentiated tissues (38,39).…”
Section: Integration Of the Transcriptome And Methylome Analysismentioning
confidence: 98%
“…Notably, overexpression of CALML3 in HLECs significantly reduced apoptosis, ROS production and intracellular Ca 2+ concentration following exposure of HLECs with 2 W/m 2 UVB irradiation for 90 min. Similar to the ubiquitous Ca 2+ sensor protein calmodulin, CALML3 acts in pre-apoptotic cells by interacting with a nuclear protein involved in chromosome fragmentation (20). The findings of the current study suggest that UVB irradiation induces apoptosis by downregulating expression of CALML3, and upregulation of CALML3 can reverse the UVB-induced damage of HLECs.…”
Section: Discussionmentioning
confidence: 54%
“…Ca 2+ is also involved in cell growth, differentiation and motility during the transformation and progression of cancer. Calmodulin like 3 (CALML3) is an epithelial-specific calcium sensing protein that highly expressed in oral mucosa, skin, breast and prostate (19,20). A previous study reported that CALML3 is regulated by short-term blockade of the MaxiK channel associated with an increase in basal Ca 2+ concentration (21).…”
Section: Introductionmentioning
confidence: 99%